Influência do programa Escola da Coluna em agentes comunitários - Nogueira, Helen Cristina; Navega, Marcelo Tavella [UNESP] (My University, 2013)
Introduction: Low back pain is characterized as a musculoskeletal disorder responsible for loss of productivity and high absenteeism of the affected individuals. Objectives: To analyze the effects of short-and long-term program of health education and therapeutic exercise in relation to quality of life, flexibility and pain intensity of community agents in Marilia city, Sao Paulo, Brazil. Methods: A total of 17 women community workers (40.29+9.97 years) were analysed. Evaluations were made in relation to quality of life, flexibility and intensity of pain before, immediately and 30 weeks after the intervention. Results: We observe the positive results of programs in six domains of quality of life questionnaire and flexibility in the short-and long-term (p<0.005). The intensity of pain showed significant reduction only in the short-term. Conclusion: The methodology used was able to improve the quality of life, flexibility and reduce pain intensity of community agents.

Introdução: A lombalgia é caracterizada como um distúrbio musculoesquelético responsável por perdas de produtividade e alto índice de absenteísmo dos indivíduos acometidos. Objetivos: Analisar os efeitos de curto e longo prazo de um programa de educação em saúde e exercícios terapêuticos em relação à qualidade de vida, flexibilidade e intensidade de dor de agentes comunitárias da cidade de Marília-SP, Brasil. Métodos: Foram avaliados 17 agentes comunitários (40,29+9,97 anos), do gênero feminino. Foram realizadas avaliações referentes à qualidade de vida, flexibilidade e intensidade de dor antes, logo após e após 30 semanas da intervenção. Resultados: Observam-se resultados positivos dos programas em seis domínios do questionário de qualidade de vida e da flexibilidade em curto e longo prazo (p<0,005). Já a intensidade de dor apresentou melhora significativa apenas em curto prazo. Conclusão: A metodologia utilizada foi capaz de melhorar a qualidade de vida, flexibilidade e intensidade de dor de agentes comunitários.
Influence of the Back School program in community agents